SOCIO-PSYCHOLOGICAL FUNCTIONS OF DECISION-MAKING IN OPTIMIZATION OF MANAGERIAL ACTIVITY (American Journal of Research in Humanities and Social Sciences, 2024)
This article analyzes the role of management in the activity of a leader and its social and psychological aspects. In the analysis, along with theoretical data, scientific and practical recommendations for optimizing the leader's activity are given.